Drug‐Drug Interaction between Oral Zamicastat and Continuous Epoprostenol Infusion at Steady‐State Conditions in Healthy Subjects - Fonseca, Marlene; Guimarães, Andreia; Gama, Helena; Magalhães, Luís; Henriques, Sara Carolina; Silva, Nuno; Almeida, Luis; Soares‐da‐Silva, Patrício (Journal of clinical pharmacology, 2024)
This study intended to evaluate the interactions between zamicastat and epoprostenol in healthy human subjects. This was a single‐center, open‐label, two‐period study. In period 1, epoprostenol 8 ng/kg/min was administered alone. In period 2, epoprostenol 8 ng/kg/min was administered following an 8‐day treatment with zamicastat. Since the initial dose of epoprostenol showed to be insufficiently tolerated, it was decreased to 6 ng/kg/min. Blood samples were collected to determine the metabolites of epoprostenol and concentrations of zamicastat and its metabolites. A total of 54 subjects were enrolled and data from 28 subjects were available for pharmacokinetic analysis. The epoprostenol plus zamicastat‐to‐epoprostenol geometric means ratio (GMR) and corresponding 90% confidence interval (CI) for Cav,ss and area under the plasma concentration–time curve from time 0 up to 16 h at steady state (AUC0‐16,ss) of the metabolites of epoprostenol were within the acceptance bioequivalence range (80.00%‐125.00%). The intrasubject coefficient of variation (ISCV) was below 10% for both parameters, on both metabolites. For zamicastat AUC0‐τ,ss, the zamicastat plus epoprostenol‐to‐zamicastat GMR and corresponding 90% CI were within the bioequivalence acceptance range, while for zamicastat Cmax,ss, the lower limit of the 90% CI was slightly below the acceptance range. For zamicastat metabolites, Cmax,ss and AUC0‐τ,ss and the zamicastat plus epoprostenol‐to‐zamicastat GMR were below the acceptance bioequivalence range. ISCV was between 30% and 41% for Cmax,ss and between 21% and 41% for AUC0‐τ,ss, for zamicastat and both metabolites. This study showed that the administration of zamicastat did not significantly modify the cardiovascular effects of epoprostenol and that the interactions between zamicastat and epoprostenol are not expected to be clinically relevant.